Risk Management for the Self-Help Home Stimulant Assistance Program, Southeast Maluku Regency - Asyani Kabalmay, Nirza; Mulyadi, Lalu; Ayu Ratna Winanda, Lila (Riviera Publishing, 2024)
The Self-Help Home Stimulant Assistance Program (BSRS) in Southeast Maluku Regency for the fiscal year 2023 faces potential risks that necessitate preventive measures to avert adverse consequences. This research aimed to identify, assess, and control the risks associated with the BSRS Program. The study employed literature reviews, interviews, and distributed questionnaires to 30 program stakeholders. The collected data underwent analysis using standard quantitative methods, encompassing risk identification, assessment, and control stages. Out of 19 risk variables, seven were categorized as Very High-Risk, five as High-Risk, and six as Moderate Risk. The research findings emphasize the imperative need for targeted control measures, such as enhancing coordination and technical activities, to mitigate and avoid identified risks in the BSRS Program implementation. The implications of this study extend beyond risk management, providing valuable insights for program improvement and sustainability. By addressing the identified risks, the BSRS Program can not only safeguard against potential negative outcomes but also enhance its effectiveness and long-term success, contributing positively to community welfare in Southeast Maluku Regency. This research serves as a foundation for informed decision-making, fostering a more resilient and robust implementation of stimulant assistance programs in the region.